Modulation of Sirt1-mTORC1 Pathway in Microglia Attenuates Retinal Ganglion Cell Loss After Optic Nerve Injury - Mou Q; Yao K; Ye M; Zhao B; Hu Y; Lou X; Li H; Zhang H; Zhao Y (Dove Medical Press, 2021)
Qianxue Mou,1 Ke Yao,1 Meng Ye,1 Bowen Zhao,1 Yuanyuan Hu,1 Xiaotong Lou,1 Huixia Li,2 Hong Zhang,1 Yin Zhao1 1Department of Ophthalmology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of China; 2Department of Physiology and Pathophysiology, School of Basic Medical Sciences, Xi'an Jiaotong University Health Science Center, Xi'an, Shaanxi, People's Republic of ChinaCorrespondence: Hong ZhangDepartment of Ophthalmology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of ChinaEmail tjyksys@163.comCorrespondence: Yin ZhaoDepartment of Ophthalmology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of ChinaEmail zhaoyin85@hust.edu.cnPurpose: Optic nerve injury (ONI) causes neuroinflammation and neurodegeneration leading to visual deficits. The response of microglia has emerged as an impactful component of etiology in neurodegeneration. This study aimed to investigate the effect of SIRT1-mTORC1 signaling pathway in microglia regulation after ONI.Methods: Cx3Cr1-CreERT2/RaptorF/F and Cx3Cr1-CreERT2/Sirt1F/F mice were used to delete Raptor and Sirt1 in microglia, respectively. Optic nerve crush (ONC) model was established to mimic ONI. PLX5622, a highly specific inhibitor of the colony-stimulating factor 1 receptor (CSF1R), is used to eliminate microglia in optic nerve. Ionized calcium binding adaptor molecule 1 (Iba1) immunostaining was used to detect microglial activation. Retinal ganglion cells (RGCs) were quantified by Nissl staining and retinal whole-mount immunostaining with RNA-binding protein with multiple splicing (RBPMS). Axonal damage was valued by transmission electron microscopy (TEM).Results: Microglial activation emerged on day 3 post ONC and was earlier than RGCs loss which occurred at day 5 after injury. Depleting microglia with PLX5622 could attenuate the loss of RGCs and axon damage after ONC. Gain- and loss-of-function studies revealed that SIRT1 determined the activation of microglia in optic nerve. In addition, microglia-specific deletion of Raptor resulted in decreased microglial activation. Interestingly, activating mTORC1 with CCT007093 could reverse the function of SIRT1 in regulating the process of microglial activation mediated RGCs loss.Conclusion: Our study reveals a potential novel mechanism of SIRT1-mTORC1 pathway in microglia regulation, and indicates a therapeutic potential for the protection of RGCs in ONI.Keywords: microglia, retinal ganglion cells, optic nerve injury, SIRT1, mTORC1